2017
DOI: 10.1016/j.anpedi.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiología y factores de riesgo de las lesiones por caídas en niños menores de un año

Abstract: The most serious injuries occur in children <3 months and from a height of >50cm, though not related to unwitnessed falls. Because the most common serious injury mechanism is the fall from the arms of the carer, from stairs, and falls in the street, these facts should be highlighted in order to avoid morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The Safe Fall programme is coherent with child safety in the event of falls as it teaches the process of falling backward by automating protective motor actions for specific parts of the body that are more often injured in falls [3,[8][9][10]: the head, the upper limbs, and the hip or lower limbs, amongst others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Safe Fall programme is coherent with child safety in the event of falls as it teaches the process of falling backward by automating protective motor actions for specific parts of the body that are more often injured in falls [3,[8][9][10]: the head, the upper limbs, and the hip or lower limbs, amongst others.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organisation [7], drew attention to the fact that falls represent the second-leading cause of death from unintentional injuries among minors throughout the world. In Spain, different studies [3,[8][9][10] have presented falls as the third most common cause of death from unintentional injuries among this population (approximately 13% of child mortality). In first place are traffic accidents (23.7%), followed closely by drownings (20%).…”
Section: Introductionmentioning
confidence: 99%
“…The Safe Fall program is aimed at safeguarding minors when they fall by training motor responses associated with the protection of those areas of the body most at risk of injury in falls: head, upper limbs, hip or lower limbs [6,7,8,9,10]. Our results suggest that through repetition of the exercises performed in the Safe Fall program, students develop automaticity of the correct motor response, as has been shown in the elderly [26].…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) has expressed concern about falls, as they are the second most common cause of children’s deaths resulting from unintentional injuries [6]. In Spain, different studies [7,8,9,10] have shown falls to be the third cause of child deaths from unintentional injuries. In Andalusia 4.3% of deaths caused from unintentional injuries derive from falls [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation